Rotary ultrasonic machining of CFRP using cold air as coolant: feasible regions - Cong, W. L.; Pei, Zhijian J.; Deines, Timothy W.; Treadwell, C. (My University, 2011)
Carbon fiber reinforced plastic (CFRP) composites are in demand for a variety of applications due to their superior properties. Drilling is involved in many CFRP applications. Experiments have been successfully conducted to use rotary ultrasonic machining (RUM) for CFRP drilling. These experiments were conducted using either cutting fluids or cold air as coolant. RUM of CFRP composites without cutting fluids can eliminate problems caused by cutting fluids, such as high cost of cutting fluids and their disposal, pollution to the environment, and harm to human health. However, dry machining (machining without cutting fluids) also has its limitations, such as burning of machined surface, more friction and adhesion between tool and workpiece, and reduction in tool life. This article presents an experimental study on feasible regions in rotary ultrasonic machining of CFRP using cold air as coolant. Three criteria (burning of machined surface, delamination, and tool blockage) were used to determine feasible regions. Each of four input variables (feedrate, tool rotation speed, ultrasonic power, and cold air pressure) was changed over a wide range so that its feasible region could be found.
Keywords: Carbon fiber reinforced plastic composite; Cold air; Drilling; Feasible region; Rotary ultrasonic machining; Vortex tube